Transformasi Strategi Bisnis UMKM Di Era Digital: Tinjauan Literatur Terhadap Efisiensi Operasional dan Adaptasi Pasar - Tezhalonika Marchela; Ragina Gita Amelia; Meitri Wulandari Djaya Negara; Rusnandari Retno Cahyani (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This literature review analyzes how digital transformation reshapes business strategies of Micro, Small, and Medium Enterprises (MSMEs/SMEs) and its implications for operational efficiency and market adaptation. The reviewed research shows that digitisation and digital transformation enhance efficiency, cost reduction, productivity, customer satisfaction, and competitive advantage, especially through social media, websites, e‑commerce, cloud services, big data, and analytics. Digital marketing and data‑driven strategies support brand awareness, product branding, customer engagement, and sustainable performance in highly competitive markets. However, MSMEs, particularly in developing countries, still face obstacles such as low digital literacy, limited financial and technological resources, and uneven digital infrastructure. Success is strongly influenced by leadership, digital competencies, human resources, integrated marketing capabilities, and supportive ecosystems including policies, training, and partnerships. The review positions entrepreneurial and product branding as central elements in leveraging digital transformation for resilient MSME growth.